2015
DOI: 10.4162/nrp.2015.9.6.619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural raw meal (NRM) on high-fat diet and dextran sulfate sodium (DSS)-induced ulcerative colitis in C57BL/6J mice

Abstract: BACKGROUND/OBJECTIVESColitis is a serious health problem, and chronic obesity is associated with the progression of colitis. The aim of this study was to determine the effects of natural raw meal (NRM) on high-fat diet (HFD, 45%) and dextran sulfate sodium (DSS, 2% w/v)-induced colitis in C57BL/6J mice.MATERIALS/METHODSBody weight, colon length, and colon weight-to-length ratio, were measured directly. Serum levels of obesity-related biomarkers, triglyceride (TG), total cholesterol (TC), low density lipoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Previous studies have shown the beneficial effects of WGC on various health problems, including the metabolic syndrome, diabetes, cardiovascular disease, stroke, hypertension, and cancer [11,12]. A recent study observed for the first time that c-oryzanol, a major component of brown rice, influenced the proliferation of muscle satellite cells [25].…”
Section: Wgc Improves Skeletal Muscle Masses and Enhances Muscle Strength In Hfd-fed Obese Micementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the beneficial effects of WGC on various health problems, including the metabolic syndrome, diabetes, cardiovascular disease, stroke, hypertension, and cancer [11,12]. A recent study observed for the first time that c-oryzanol, a major component of brown rice, influenced the proliferation of muscle satellite cells [25].…”
Section: Wgc Improves Skeletal Muscle Masses and Enhances Muscle Strength In Hfd-fed Obese Micementioning
confidence: 99%
“…Whole grain cereal (WGC)-based food products are a source of beneficial minerals, vitamins, and other phytochemicals, which are required for to maintain health, as well as of macronutrients required for body maintenance and support [11]. Previous studies have shown the functional effects of WGC on various health problems, including the metabolic syndrome, diabetes, cardiovascular disease, stroke, hypertension, and cancer [11,12]. The present study demonstrates that WGC attenuates obesity-related skeletal muscle atrophy by stimulating PI3K/Akt pathway signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathogenesis of UC is not completely understood, immune disorders caused by complications of genetic and environmental factors (e.g., eating habits and intestinal bacterial flora) are considered to be responsible for the development and exacerbation of UC. 1,2) Intake of a high-fat diet has been shown cause an elevation of inflammatory cytokines (e.g., tumor necrosis factor (TNF)-α and interleukin (IL)-1β) in dextran sulfate sodium (DSS)induced colitis, 3) a pathological model of UC, and is associated with the development of UC. 4) In fact, the prevalence of UC is rising, particularly in countries where the intake of high-fat diets is increasing.…”
mentioning
confidence: 99%
“…Commercially-available Saengshik mainly comprises 30-60 types of whole grains, vegetables, seaweeds, mushrooms, and other minor plant-based ingredients. Due to the process of freeze-drying or low-temperature drying of its ingredients, Saengshik preserves various nutrients, including minerals, vitamins, and phytochemicals in raw materials (2)(3)(4)(5)(6)(7)(8)(9). Additionally, Saengshik consumption has increased based on its advantage of allowing convenient consumption of various plant-derived raw materials.…”
Section: Introductionmentioning
confidence: 99%
“…Saengshik also exhibits various bioactive functions, including antidiabetic (4,5), anti-dyslipidemic, antioxidant (4,6), and anticancer (7,8) activities. Furthermore, Shin et al (9) reported that Seangshik supplementation attenuated colitis in murine models of inflammatory bowel disease. These beneficial effects might be attributed to the functional ingredients of plant-based foods, such as phytochemicals, minerals, vitamins, and dietary fibers.…”
Section: Introductionmentioning
confidence: 99%